Probing the Binding Requirements of Modified Nucleosides with the DNA Nuclease SNM1A - Eva-Maria Dürr; Joanna F. McGouran (Molecules, 2021)
SNM1A is a nuclease that is implicated in DNA interstrand crosslink repair and, as such, its inhibition is of interest for overcoming resistance to chemotherapeutic crosslinking agents. However, the number and identity of the metal ion(s) in the active site of SNM1A are still unconfirmed, and only a limited number of inhibitors have been reported to date. Herein, we report the synthesis and evaluation of a family of malonate-based modified nucleosides to investigate the optimal positioning of metal-binding groups in nucleoside-derived inhibitors for SNM1A. These compounds include ester, carboxylate and hydroxamic acid malonate derivatives which were installed in the 5′-position or 3′-position of thymidine or as a linkage between two nucleosides. Evaluation as inhibitors of recombinant SNM1A showed that nine of the twelve compounds tested had an inhibitory effect at 1 mM concentration. The most potent compound contains a hydroxamic acid malonate group at the 5′-position. Overall, our studies advance the understanding of requirements for nucleoside-derived inhibitors for SNM1A and indicate that groups containing a negatively charged group in close proximity to a metal chelator, such as hydroxamic acid malonates, are promising structures in the design of inhibitors.